Temporal Trends and Effects of Noise on Upsweep Calls of Eastern South Pacific Southern Right Whales - Jacobs, Ellen Rose; Landea-Briones, Rafaela; Sayigh, Laela (Frontiers in Remote Sensing, 2022)
Eastern South Pacific southern right whales (ESPSRW) are a subpopulation of southern right whales (Eubalaena australis) off the coasts of Peru and Chile recognized by the International Union for the Conservation of Nature (IUCN) as critically endangered as a result of heavy whaling efforts in the late 18th to 20th centuries. Most recent population estimates put their numbers around 50 individuals. To test for the efficacy of passive acoustic monitoring of this population, we recorded five months of continuous acoustic data (January 2012-June 2012) off the southwestern tip of Isla de Chiloé. To test for trends in occurrence, we identified 11,313 individual ESPSRW upsweep calls, which have been associated with maintaining contact with conspecifics. Calls increased over the course of the deployment and peaked between April and June, indicating an increase in habitat. A clear diel pattern in which upsweep calls were predominately detected during dusk and night hours was identified, indicating ESPSRW are likely foraging during daylight hours, as upsweep calls are inversely related to foraging behavior. We quantified noise levels in the frequency range of their communication (100 Hz third octave) to understand the change in active space whales may be experiencing. We measured noise levels from 90 dB re 1 µPa to 111 dB re 1 µPa (5th and 95th percentile), a 21 dB fluctuation that results in an order-of-magnitude decrease in active space area. We identified sources of high noise at or above the 75th percentile as predominately blue whale calls (occurring in 71.6% of total sampled minutes) and ship noise (occurring in 69.4% of total sampled minutes). Ship noise was responsible for outliers in excess of 140 dB re 1 µPa. In a population as diminished as ESPSRW, such disruptions of their communication range could result in significant barriers to maintaining contact with conspecifics. Passive acoustic monitoring is a powerful tool for monitoring populations as rarely sighted as ESPSRW. Understanding trends in presence and behavior as well as potential sources of disruption of their calling behavior is vital to determining conservation measures that will be most effective toward helping this critically endangered population.